TECHNOLOGIES AND HUMAN CONVERGENCE - Xaytboyev Boburjon Xamzayevich (European Science Publishing, 2023)
This article explores the dynamic interplay between evolving technologies and human convergence, aiming to understand the impact on society, the challenges posed, and the ethical considerations that arise. By conducting a comprehensive literature analysis, we delve into the existing discourse surrounding this phenomenon, presenting various perspectives and insights. The methods section outlines the approach taken to gather and synthesize information, while the results section highlights key findings. The discussion section critically examines the implications and potential future developments, and the conclusions and suggestions provide a thoughtful reflection on the path forward.
Keywords: Technologies, human convergence, innovation, society, artificial intelligence, human-machine interaction, future trends, ethical considerations.